Epididymis-specific pathologic disorders in rats exposed to gossypol from weaning through puberty - de Andrade, Sergio Faloni; Oliva, Samara Urban; Klinefelter, Gary Robert; Kempinas, Wilma de Grava (Taylor & Francis Inc, 2006)
Previous work in our laboratory revealed that the pubertal period of reproductive development in the male rat was particularly vulnerable to gossypol exposure, with a higher frequency of round structures in the lumen of the cauda epididymidis in the treated rats. Herein, we utilized hemicastration and electron microscopy to confirm that the epididymis is a definitive target of gossypol. Although exposure to gossypol from weaning through puberty caused a significant decrease in daily sperm production, as well as in the concentration of sperm in the epididymis, serum testosterone levels and reproductive organ weights were not altered. In gossypol treated rats, sperm morphology was compromised severely, but the epithelium in testis and epididymis appeared morphologically normal. Ultrastructural examination revealed that round structures, present only in gossypol exposed males, represented: (1) principal cells exfoliated from the epididymal epithelium; (2) epididymal epithelial cell cytoplasm containing degenerating sperm; and (3) degenerating epithelial cells, consisting of vesicles and particles of different sizes, forms and densities. Taken together, the data confirm that gossypol targets the epididymis, disturbing both the structure and function of this organ, and presumably disrupts sperm maturation.
Keywords: epididymis pathology; male reproductive toxicology; gossypol; puberty; electron microscopy; rat